Cooperative Law and the Social and Solidarity Economy in France - Hiez, David (Cooperativismo & Desarrollo, 2019)
Cooperative law has a long history in France, whereas social and solidarity economy is far more recent, since it has been legally established by the legislator in 2014. As cooperative law is the most solid legal form of social and solidarity economy enterprises, it is interesting to assess its influence on the establishment of the law of 2014, as well as to examine its potentialities for future. By an analytical and critical appraisal, this paper is an occasion to highlight, five years after its adoption, the law of 2014, considered positively by all the authors at that time